ONLINE TEACHING AND LEARNING DURING THE CORONAVIRUS PANDEMIC: ADVANTAGES AND DISADVANTAGES IN HIGHER EDUCATION - Chayaporn Saranpuetti; Piyatida Khajornchaikul; Vallerut Pobkeeree (Universitas Airlangga, 2022)
Everything is changing rapidly and the development of technology and information has changed significantly in the last few decades. Education, like other aspects of society, needs to change and adapt appropriately. Online teaching and learning is a new approach for the authors to use information technology via distance learning programs, especially the way relationships and interactions altered between students and teachers or instructors when the Coronavirus disease (COVID-19) pandemic occurred last year. Mahidol University responded to the situation rapidly and announced that academics can use online teaching of students free of charge. The authors of this paper have identified the advantages and disadvantages we have encountered while applying this method of instruction. The online program has made teaching possible but it has disadvantages which may decrease the quality of education. Nevertheless, it was used to replace traditional teaching methods by utilizing the web–based program, Webex Meetings, across the whole university. This new approach has changed and opened horizons earlier than the authors thought and far beyond our beliefs concerning traditional education methods for future generations.